Post-translational modification gene signatures implicate FBXW7 in immune and vascular dysregulation of Moyamoya disease - Yu, Xiaofan; Wang, Zicong; Zhou, Zhenyu; Liu, Yutong; He, Shihao; Zhao, Yuanli (Frontiers in Genetics, 2025)
BackgroundMoyamoya disease (MMD) is a rare cerebrovascular disorder characterized by progressive stenosis and occlusion of intracranial arteries and abnormal collateral vessel formation. However, the underlying molecular mechanisms are not completely understood. Post-translational modifications (PTMs) are essential regulators of protein function and signal pathway, yet their roles in MMD have not been fully explored.MethodsTranscriptomic datasets from an independent cohort and public datasets were integrated. Differential expression analysis, weighted gene co-expression network analysis (WGCNA), and machine learning were applied to identify candidate biomarkers. Functional enrichment, immune infiltration analysis, and protein-protein interaction networks were constructed. Validation of expression and diagnostic performance of the selected feature genes was performed across training and test sets. Molecular docking and dynamics simulations were conducted to evaluate the potential drug molecules. In addition, enzyme-linked immunosorbent assay (ELISA) was performed to measure serum FBXW7 levels in an independent cohort (n = 20), and in vitro experiments including scratch assay and EdU assays were conducted to assess vascular smooth muscle cell (HBVSMC) migration and proliferation after FBXW7 knockdown.Results1,547 differentially expressed genes were identified, and 4 genes were identified as feature genes with diagnostic significance, using machine learning and validation. With functional annotations, pathways including ubiquitination, SUMOylation, and neddylation were identified. HLA-A was upregulated and strongly associated with immune infiltration. FBXW7 was downregulated and may promote aberration in vascular smooth muscle cell proliferation and migration. Furthermore, molecular docking and dynamic simulations jointly confirmed the stability of the FBXW7-MRK-003 complex. ELISA results showed that serum FBXW7 levels were significantly decreased in MMD patients compared with healthy controls. Consistently, in vitro assays demonstrated that HBVSMC migration and proliferation were markedly enhanced in the si-FBXW7 group compared with the si-NC group.ConclusionOur study identifies PTM-related genes involving the development of MMD. Especially, we found that FBXW7 and HLA-A bridging immune dysregulation and vascular dysfunction. Our work provide innovative insights into mechanisms of MMD pathogenesis and candidate therapeutic targets for precision therapy of MMD.